Overview of Quality of Life in Pet Owners Elderly - Nasir, Dian Oktaviana; Widyastuti, Widyastuti (Polteknik Ilmu Pemasyarakatan, 2024)
The elderly experience a decline in physical, psychological and social functions that can affect quality of life but can be improved through close figures such as pets. This study aims to determine how the quality of life is described in elderly pet owners. This research uses a qualitative method of case study approach with theory-driven analysis. Data collection through interviews and observations of three elderly people aged 60 years and over. The results obtained show that the elderly feel satisfaction in the dimensions of physical well-being, social well-being, emotional well-being development and activity while having pets. Pets can serve as a source of social support that provides both physical and psychological benefits for the elderly. In material well-being, the elderly show less satisfaction due to unstable financial conditions. However, pet care can be adjusted to the financial condition of the elderly. This research can be a reference for the government to provide financial assistance, especially to the elderly.